Estandarización de procesos industriales de mecanizado en función de los puestos de trabajo en los tornos paralelos de Ingeniería Industrial - Esparza Sisalema, Jonathan Fabián (2024)
This research focuses on standardizing machining processes on parallel lathes within the context of Industrial Engineering. Specifically, it analyzes the processes of facing and turning, identifying the main issue as the need for more standardization in machining processes due to the absence of detailed technical documentation in the UNACH Machine and Tool Laboratory. This lack leads to operational inefficiencies, including unproductive times, unnecessary movements, and material waste, exacerbated by the absence of a method that specifies procedures, thereby limiting users’ practice hours. The investigation begins with observation to identify and record the causes of inefficiencies through time and motion studies. Flowcharts describe the activities and elements involved in facing and turning processes, allowing for an analysis of unproductive times and unnecessary movements. The research proposes standardized procedures to improve machining operation efficiency, eliminate unproductive times, and optimize material usage. These improvements significantly reduce machining execution times, achieving a 50.12% reduction for facing and a 33.45% reduction for turning processes, contributing to the continuous improvement of machining processes in the Industrial Engineering program.